RICE FOOD ASSISTANCE ADMINISTRATION PROCEDURES BULOG AT PT POS INDONESIA (PERSERO) CIREBON CITY POST OFFICE - Yulia Mujiaty; Deasy Novayanti; Siti Nurjanah; Darma Wijaya; Noviana Putri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Administration Procedures for Bulog Rice Food Assistance at PT Pos Indonesia (Persero) Cirebon City Post OfficeThe Bulog rice food assistance program is one of the effective ways to maintainpurchasing power and food inflation control efforts and has an important role in community welfare, especially for low-income economic groups. Administrative procedures are very important in carrying out an activity, because without administrative procedures the objectives of the activity to be achieved will not runwell. The Cirebon City Post Office is one of the branches that distributes this rice food assistance. The purpose of this study was to determine the flow of the bulog rice food assistance administration process at the Cirebon city post office. The method of data collection in the preparation of the Final Project is the method of observation, interviews, and literature study with the analysis method in the form of qualitative analysis, namely the method of analyzing data. The results of the study explain that the food aid administration process is from the national food agency sending recipient data such as a summons to the Indonesian post until the recipient receives the rice. The documents used in this rice food assistance administration procedure are the summons and the recipient's original KTP. Obstacles in food aid administration procedures that often occur are obstacles from the recipient community and from the post office itself. Based on these constraints, the Company's suggestion is to conduct periodic evaluations of the rice food assistance administration procedures to identifyshortcomings and make necessary improvements.